Upper Extremity Deep Vein Thrombosis after Clavicle Fracture and Immobilization - Sung Jin Kim; Dae Sung Ma; Sung Youl Hyun; Yang Bin Jeon; Seok Joo; Ahram Han (Journal of Trauma and Injury)
Upper extremity deep vein thrombosis (DVT) is an unusual condition compared to lower extremity DVT, and it represents about 10% of all DVTs. We report a case of upper extremity DVT after clavicle fracture and immobilization.